RASIONALITAS PENAFSIRAN IBNU ‘ATHIYYAH - Abdullah Karim (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2009)
Binyamin Abrahamov defines rationality as “treating anyissues by using reason, but without giving reason priority.” Thus, interms of Qur‟anic interpretation, rationality means using reason orijtihâd in interpreting the Qur‟an without prioritizing the reason it self.For Ibn „Athiyyah, in addition to the existing authoritative reports of theprophetic tradition, reason is necessary in interpreting the Qur‟an. Thisis because, the text of the Qur‟an contains words whose meanings arespecific, ambiguous or even contradictory. However, this rationality ofinterpretation is only applied to the meaning of words or structure of theQur‟anic sentences, but it does not include the use of analogy (qiyâs)employed in the methodology of Islamic law.